Burden and Quality of Life of Family Caregivers of Stroke Patients. Issue 2 (3rd April 2018) - Caro, Camila Caminha; Costa, Jacqueline Denubila; Da Cruz, Daniel Marinho Cezar
ABSTRACT: The purpose of this study was to identify the level of burden and quality of life of family caregivers of stroke patients and to investigate the correlation between burden, quality of life (including physical, social, psychological, and environmental domains), age of caregivers, and the care period. A descriptive correlational cross-sectional study was performed, with a convenience sample of family caregivers ( n = 30) of stroke patients in São Paulo, Brazil. Data were collected using a questionnaire on participants' characteristics, the Zarit Burden Interview Scale (ZBIS), and the World Health Organization Quality of Life-BREF (WHOQOL-BREF) instrument . A descriptive analysis was performed, and correlations between variables were analyzed using Pearson's product-moment correlation coefficient. The average burden score on the ZBIS was 29.6, representing a moderate burden, and the average overall quality of life score on the WHOQOL-BREF was 62.06%, which indicates moderate quality of life. A significant weak negative correlation was observed between burden and environmental domains ( r = −0.470; p =.009), quality of life ( r = −0.414; p =.023), and physical domains ( r = −0.394; p =.031). No significant correlations were found between burden and quality of life, and variables in the psychological and social domains, age of caregivers, or care period. Caregivers for stroke patients presented with moderate levels of burden and reduction in quality of life. Levels of burden correlated negatively with environmental domains, quality of life levels, and physical domains; however, these correlations were weak, indicating the possible interference of other factors.